Implementasi nilai-nilai Pancasila dalam praktik demokrasi di Indonesia - Oktantyo, Adi Widya (Maliki Interdisciplinary Journal, 2025)
Pancasila, as the foundation of the Indonesian state, plays a crucial role in shaping the democratic system today. While Indonesia adopts a democratic system, the values of Pancasila guide political and social decision-making. Indonesian democracy seeks to integrate the principles of freedom, justice, and public participation with the noble values of Pancasila. However, its implementation faces challenges, such as identity politics, corruption, and social inequality. This paper aims to analyze the implementation of Pancasila values within Indonesia's democratic system and identify obstacles in applying democracy in line with Pancasila’s spirit. Through a qualitative approach, this study examines the relationship between Pancasila and democracy, as well as factors affecting its application. The findings aim to provide recommendations to strengthen Indonesian democracy by upholding Pancasila values in political and social life.